2004
DOI: 10.1128/cdli.11.6.1165-1170.2004
|View full text |Cite
|
Sign up to set email alerts
|

Utility ofSchistosoma bovisAdult Worm Antigens for Diagnosis of Human Schistosomiasis by Enzyme-Linked Immunosorbent Assay and Electroimmunotransfer Blot Techniques

Abstract: Immunodiagnostic methods based on the detection of antibodies continue to be the most effective and practical methods for the diagnosis of imported schistosomiasis. Schistosoma bovis is a species whose final natural hosts are bovines, ovines, caprines, and small wild ruminants. Different studies have demonstrated the analogies existing between S. bovis and other Schistosoma species which affect humans. The objective of this work was to evaluate the utility of S. bovis adult worm antigens (AWA) for the diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 30 publications
0
16
0
1
Order By: Relevance
“…Most likely, species-specific heterogeneities of the utilized antigens were responsible for the observed differences. Although it has been shown that S. mansoni proteins used for serological testing have sufficient similarity to allow serodiagnosis of S. haematobium infections (32), some species-specific differences remain, favoring test systems using homologous antigens (2,19,22,30,36,39,42). Nevertheless, species-specific performance differences were not determined only by the utilized antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Most likely, species-specific heterogeneities of the utilized antigens were responsible for the observed differences. Although it has been shown that S. mansoni proteins used for serological testing have sufficient similarity to allow serodiagnosis of S. haematobium infections (32), some species-specific differences remain, favoring test systems using homologous antigens (2,19,22,30,36,39,42). Nevertheless, species-specific performance differences were not determined only by the utilized antigens.…”
Section: Discussionmentioning
confidence: 99%
“…The Specific Worm Antigen Product (SWAP) was obtained as previously described (Pardo et al 2004). ELISAs were performed by coating polystyrene plates (Costar) with 0.1 ml of 10 mg/ml SWAP in Phosphate Buffer Saline (PBS) overnight at 4°C.…”
Section: Quantification Of Specific Antibodies Against S Mansonimentioning
confidence: 99%
“…This assay employed the qualitative enzyme immunoassay technique. 20 The crude eggsoluble antigen (50 μL) of 3 μg/mL diluted 1:200 in carbonate buffer (pH 9.6) was used to coat the microtiter well plates and then incubated overnight at 4 °C. This was followed by washing of plates with 0.05% Tween 20 in PBS-Tween 20, thrice.…”
Section: Serological Assaysmentioning
confidence: 99%